Associations of content and gene polymorphism of macrophage inhibitory factor-1 and chronic hepatitis C virus infection - Yang, Xun-Jun; Wang, Xiao-Ou; Chen, Yao; Ye, Song-Dao (World journal of gastroenterology : WJG, 2020)
The expression of macrophage inhibitory factor-1 (MIC-1) is increased in peripheral blood of patients with chronic hepatitis and liver cirrhosis. However, whether gene polymorphism is correlated with relevant diseases is not yet reported. To explore the correlation between gene polymorphism in exon region and chronic hepatitis C virus (HCV) infection. This case-control study enrolled 178 patients with chronic hepatitis C (CHC) in the case group, and 82 healthy subjects from the same region who had passed the screening examination comprised the control group. The genotypes of rs1059369 and rs1059519 loci in the gene exon were detected by DNA sequencing. Also, the MIC-1 level, liver function metrics, liver fibrosis metrics, and HCV RNA load were determined. Univariate analysis was used to compare the differences and correlations between the two groups with respect to these parameters. Multivariate logistic regression was used to analyze the independent relevant factors of CHC. The plasma MIC-1 level in the CHC group was higher than that in the control group ( < 0.05), and it was significantly positively correlated with alanine aminotransferase, aspartate aminotransferase (AST), type III procollagen N-terminal peptide (known as PIIINP), type IV collagen, and HCV RNA ( < 0.05), whereas negatively correlated with total protein and albumin ( < 0.05). The genotype and allele frequency distribution at the rs1059519 locus differed between the two groups ( < 0.05). The allele frequency maintained significant difference after Bonferroni correction ( < 0.05). Logistic multiple regression showed that AST, PIIINP, MIC-1, and genotype GG at the rs1059519 locus were independent relevant factors of CHC ( < 0.05). Linkage disequilibrium (LD) was found between rs1059369 and rs1059519 loci, and significant difference was detected in the distribution of haplotype A-C between the CHC and control groups ( < 0.05). Meanwhile, we found the MIC-1 level trend to increase among rs1059519 genotypes ( = 0.006) and the level of MIC-1 in GG genotype to be significantly higher than CC genotype ( = 0.009, after Bonferroni correction). Plasma MIC-1 level was increased in CHC patients and correlated with liver cell damage, liver fibrosis metrics, and viral load. The polymorphism at the gene rs1059519 locus was correlated with HCV infection, and associated with the plasma MIC-1 level. G allele and GG genotype may be an important susceptible factor for CHC.